The influence of variation in cement characteristics on workability and strength of SCC with fly ash and slag additions. (30th January 2018) - Almuwbber, Omar; Haldenwang, Rainer; Mbasha, Willy; Masalova, Irina
Highlights: The interaction of mineral and chemical admixture with different cements for self-compacting concrete was assessed. The sensitivity of self-compacting concrete properties on cement characteristics was shown. A procedure to determine the self-compacting concrete sensitivity was suggested. Abstract: The effects of fly ash and slag on fresh and hardened properties of self-compacting concrete (SCC) were investigated using four CEM I 52.5 N cements produced at different factories according to ASTMC150, two polycarboxylate-acid based superplasticisers, two class F fly ashes and one slag. The differences in the cement characteristics were enough to affect the SCC flow properties. The compatibility of cement and admixtures depended mostly on the concentration of C3 A, C2 S/C3 S ratio, the specific surface area of the cement and the type of superplasticiser used. A protocol to assess the sensitivity of a SCC mix design to a type of cement is proposed.